Effects of treatment with a combination of cardiac rehabilitation and bosentan in patients with pulmonary Langerhans cell histiocytosis associated with pulmonary hypertension. (December 2014) - Fukuda, Yusuke; Miura, Shin-ichiro; Fujimi, Kanta; Yano, Masaya; Nishikawa, Hiroaki; Yanagisawa, Jun; Hiratsuka, Masafumi; Shiraishi, Takeshi; Iwasaki, Akinori; Saku, Keijiro
Pulmonary hypertension (PH), which is classified as group 5 in the clinical classification of PH, is sometimes a complication of Pulmonary langerhans cell histiocytosis (PLCH), and is associated with high mortality. A 36-year-old woman had suffered from severe dyspnea 9 years previously and was diagnosed with PLCH and was on a waiting list for a lung transplant. Right heart failure had been observed and the mean pulmonary artery pressure was over 40 mmHg. The patient was diagnosed as PLCH with PH. After combined treatment with exercise rehabilitation and bosentan for 6 months, the cardiothoracic ratio, brain natriuretic peptide, and bodyweight were significantly decreased (cardiothoracic ratio from 43 to 38%, brain natriuretic peptide from 284 to10 pg/ml and bodyweight from 63 to 58 kg). Six-minute walk test also improved from 214 to 275 meters and the SF36 score for screening of depressive and anxiety disorders was improved. This is the report demonstrating the efficacy and safety of cardiac rehabilitation in combination with bosentan in a single patient with PLCH associated with PH.